The status of research on Lake Victoria fisheries: Historical and current data on fisheries and the lake environment - Outa, Nicholas; Mungai, Dan; Ogello, Erick (My University, 2019)
Lake Victoria which is the second largest freshwater lake in the world supports a large population living around it through provision of food; fish and employment; both directly and indirectly. Due to its varied uses, human intervention within the lake and its catchment has caused several ecological changes in the recent years which have had profound effects on its resources. Historical and recent data within the lake show an enormous change in the diversity of the fish species as well as environmental and ecological changes. Some of the reasons cited for the changes in biodiversity within the lake are: the introduction of alien fish species like Nile perch (Lates niloticus) and Nile tilapia (Oreochromis niloticus) into the lake, habitat loss and the cultural eutrophication. Several research projects like Lake Victoria Management programme (LVEMP) and Lake Victoria Fisheries Organization (LVFO) have been formed to help address some of these problems with varied levels of success. There is therefore an urgent need for management measures based on sound scientific research to be taken in order to curb this loss of ichthyodiversity within the lake and to save the livelihoods of the people who are dependent on the lake. Owing to the importance of the lake to the livelihoods of the people around the lake and beyond, there is need for concerted effort by all stakeholders in trying to halt the degradation and other negative environmental and ecological changes within the lake. Ecosystem approach to conservation is the way forward in the management and sustainable utilization of the fisheries and other resources within the lake.
Keywords: Eutrophication; Extenction; Lake Victoria